SIFAT-SIFAT BILANGAN RAMSEY MULTIPARTIT-UKURAN UNTUK GRAF MULTIPARTIT SEIMBANG LENGKAP - Haida Fitri, Haida Fitri (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2016)
For complete balanced multipartite graphs  and , the size multipartite Ramsey number  is the smallest natural number  such that an arbitrary colouring of the edges of , using the two colours red and blue, necessarily forces a red  or a blue  as subgraph. In this paper, also discuss about the properties of size multipartite Ramsey  numbers in complete balanced multipartite graphs such as, partial existence propertie, growth properties, gaps propertie and asymptotic limits propertie.Keywords:  Set/ size multipartite Ramsey numbers, multipartite graph, balanced             multipartite graph, complete balanced multipartite graph.